THE APPLICATION OF LEADERSHIP MOTIVATION FOR STUDENT OF LAW IN TRANSLATING LOCAL TO ENGLISH LANGUAGE WITH ASSISTANT LECTURE SYSTEM - Wirawan Pamuji (Lembaga Pengembangan Kinerja Dosen, 2022)
An attempt of diminishing final disability, many students of University have resembled a step of less spirit of Leadership, it is because likely that the goal is to master students in understanding subject according to the meaning, not to the functions. Furthermore, since communication is a process, it is insufficient for students to simply knowledge of target language forms, meaning and function to teach in easy way is still being puzzled as the creator of Class Explanatory is only a Lecturer and the potential student is not yet immersed to be right hand of Lecturer himself as a second speaker. Classical methods are very often because of meaningful learning or contextualized teaching learning consideration, in this term we would like to analyze about law students English material which needs an urgency to read a case text for court proceeding as it requires intensive understanding inferential reading to deepen the meaning, therefore it is inevitable to translate local language to English contextually to face moot Court or Simulation Court as The Translated Document could be authentically or Contextually delivered in speech before court officials as a Court Sentence to Inform Foreign Court Officials about Justice Decision. That in this case, lecturer commands students to collect difficult words of Indonesian then they would translate them all in English then Lecture orders them to create an article from collected translates words and changes the words into sentence in the article then Lecture opens election who can lead the classroom as potentially find Indonesian Court Difficult Words Translated in English with Lecture assistant to translate it, the assistant lecture is not mere in duty to collect difficult words from students but also translate it into English as he could before noting it Assistant Lecture felt that he was positioned as a Guidance of the class as he felt motivated to increase his Leadership in maintaining Difficult Words and explained then he was proud for that.